Analysis of Marketing Relationships on Customer Loyalty in the Service Sector - Evi Sirait; Ina Sawitri; Adyk Marga Raharja; Andriya Risdwiyanto; Djoko Widagdo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of relationship marketing on customer loyalty in the service sector. Relationship marketing is an important strategy in the service business world because it can build long-term relationships between companies and customers through communication, trust, commitment, and complaint handling. Customer loyalty is a crucial factor for the sustainability of service companies because loyal customers tend to make repeat purchases, provide positive recommendations, and are less likely to switch to competitors. This study uses a quantitative approach with an associative research type. Data were obtained by distributing questionnaires to customers in the service sector using a purposive sampling technique. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, and linear regression analysis to determine the effect of relationship marketing on customer loyalty. The research results show that relationship marketing has a positive and significant impact on customer loyalty. The variables of communication, trust, commitment, and complaint handling have been shown to contribute to increasing customer loyalty in the service sector. Customer trust is the most dominant factor in shaping loyalty because customers tend to maintain relationships with companies that are able to provide consistent and reliable service. Furthermore, effective communication and good complaint handling can also increase customer satisfaction, thereby strengthening long-term relationships between companies and customers. Therefore, service companies need to optimally implement relationship marketing to increase customer loyalty and create a competitive advantage amidst increasingly fierce business competition.